The role of oxidative DNA damage, DNA repair, GSTM1, SOD2 and OGG1 polymorphisms in individual susceptibility to Barrett's esophagus - (:unkn) unknown (SAGE PUBLICATIONS INC, 2010)
Determination of the genetic alterations, which play a role in the etiology of Barrett's esophagus (BE), could help identify high-risk individuals for esophageal adenocarcinoma (EA). The aim of the present study was to investigate the role of oxidative DNA damage, glutathione (GSH) concentration as oxidative stress parameters and DNA repair capacity, GSTM1, SOD1 Ala16Val and OGG1 Ser326Cys genetic polymorphisms as individual susceptibility parameters in the etiology of BE. The study groups comprised BE patients who were clinically diagnosed (n = 40) and a healthy control group (n = 40). Basal DNA damage, pyrimidine and purine base damage after H(2)O(2) induction, H(2)O(2) sensitivity, DNA repair capacity, oxidized pyrimidine and purine base damage repair were evaluated in peripheral blood lymphocytes with a modified comet assay using specific endonucleases (Endo III and Fpg). Polymerase chain reaction-restriction length polymorphism (PCR-RFLP)-based assays were used for genotyping. The patient group showed elevated levels of basal DNA damage, pyrimidine base damage and H(2)O(2) sensitivity as compared to controls (p<.05). DNA repair capacity, oxidized pyrimidine and purine base damage repair capacity, were not statistically different between patients and controls. GSH concentration was found to be significantly lower in smoking patients than in the controls (p<.05). None of the genetic variations changed the risk of having BE disease. However, patients carrying the variant OGG1 Cys allele showed elevated levels of pyrimidine base damage as compared to patients carrying the wild-type OGG1 Ser (p<.05). The results of this study point to a role of oxidative DNA damage in BE. However, DNA repair capacity, GSTM1, SOD1 Ala16Val and OGG1 Ser326Cys genetic polymorphisms appeared to play no role in the individual susceptibility to this disease.
Keywords: Barrett's esophagus; oxidative DNA damage; DNA repair; comet assay; individual susceptibility; SUPEROXIDE-DISMUTASE MNSOD; GLUTATHIONE S-TRANSFERASES; GENETIC POLYMORPHISMS; REFLUX ESOPHAGITIS; MALIGNANT-TRANSFORMATION; MOLECULAR EPIDEMIOLOGY; CANCER SUSCEPTIBILITY; BREAST-CANCER; RISK-FACTORS; BASE DAMAGE